2021
DOI: 10.1002/pen.25627
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in nano‐pattern replication of injection molding by polyamide/dendrimer blend

Abstract: In general, lower viscosity of materials leads to desirable nano‐pattern replication characteristics in injection molding processes. However, such materials do not meet the properties required for manufacturable products owing to their poor mechanical properties. In this study, we blended a small amount of dendrimer with high‐viscosity polyamide 6 to lower viscosity and enhance flowability of the polymer blend while maintaining desirable mechanical properties. It was observed that the flowability of the polyam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…First, nylon 6 chains and polyethylene chains with a polymerization degree of 15 were constructed, and 36 PA6 chains and 120 PE chains were repeated as the polymer layers of the composite interface model (Figure 1). The density of the PA6 layer was set to 1.06/cm 3 , and PE was 0.83 g/cm 3 . Then, a face-centered cubic (FCC) structure model with dimensions of 5.4 nm  5.4 nm  4 nm was constructed with Al as the metal substrate.…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, nylon 6 chains and polyethylene chains with a polymerization degree of 15 were constructed, and 36 PA6 chains and 120 PE chains were repeated as the polymer layers of the composite interface model (Figure 1). The density of the PA6 layer was set to 1.06/cm 3 , and PE was 0.83 g/cm 3 . Then, a face-centered cubic (FCC) structure model with dimensions of 5.4 nm  5.4 nm  4 nm was constructed with Al as the metal substrate.…”
Section: Model Constructionmentioning
confidence: 99%
“…In nano‐molding, the surface treatment of the metal substrate to form a relatively homogeneous nano‐cavity structure can be achieved by sandblasting, [ 3 ] laser processing, [ 4 ] chemical etching, and nano‐molding techniques, through which micro‐nanosized structures can be prepared. [ 5 ] As a result, the contact area of polymer melts on the metal surface is enriched, contributing to the formation of mechanical interlocking [ 6 ] to improve the joining strength at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…4b that with the increase of PAMAM content, T g and T m gradually decreased to 52.83 °C and155.82 °C, respectively, T cc decreased rst and then increased, reaching the minimum value of 100.35 °C when the content was 3phr. It suggested that the addition of PAMAM could play a plasticizing role in accelerating the movement ability of molecular segments, reduce the hydrogen bond of CA, improve the molecular chain movement and crystallization capacity [33]. The crystallization enthalpy increased with the addition of PAMAM, while the melting enthalpy increased rst and then decreased, reaching the maximum at 3 phr.…”
Section: Crystalline Propertiesmentioning
confidence: 99%
“…Dendrimers are a special class of nano-sized artificial macromolecules with a symmetrical structure, a high degree of branching, a globular architecture, an extremely low polydispersity, and a well-defined molecular weight. 1 Due to their unique structural features and excellent properties, they are widely used as nanocarriers for drug delivery, 2,3 catalysts, 4 nanosensors, [5][6][7] MRI contrast agents, [8][9][10] modifiers of rheological properties [11][12][13][14][15] and more. The development of synthesis strategies has led to the appearance of functionalized dendrimers (FD).…”
Section: Introductionmentioning
confidence: 99%